2020
DOI: 10.1371/journal.pone.0230578
|View full text |Cite
|
Sign up to set email alerts
|

Auditory chain reaction: Effects of sound pressure and particle motion on auditory structures in fishes

Abstract: Despite the diversity in fish auditory structures, it remains elusive how otolith morphology and swim bladder-inner ear (= otophysic) connections affect otolith motion and inner ear stimulation. A recent study visualized sound-induced otolith motion; but tank acoustics revealed a complex mixture of sound pressure and particle motion. To separate sound pressure and sound-induced particle motion, we constructed a transparent standing wave tubelike tank equipped with an inertial shaker at each end while using X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 56 publications
3
16
0
Order By: Relevance
“…We focused on the otophysan saccular otoliths for two reasons. First, this structure showed a rotational movement induced by sound pressure in a previous study which could be easily identified even in radiographs (Schulz-Mirbach et al, 2020) and was also in line with the motion pattern hypothesized by experts in the last century (von Frisch, 1938, de Burlet, 1929, Wohlfahrt, 1932. Second, the 0° in-phase and 180° out-of-phase conditions in the previous study clearly differed from each other by the evoked motion pattern of this otolith with the rotational motion only identifiable under the 0° in-phase condition.…”
Section: Segmentation and Generating The 3d Surfacessupporting
confidence: 85%
See 4 more Smart Citations
“…We focused on the otophysan saccular otoliths for two reasons. First, this structure showed a rotational movement induced by sound pressure in a previous study which could be easily identified even in radiographs (Schulz-Mirbach et al, 2020) and was also in line with the motion pattern hypothesized by experts in the last century (von Frisch, 1938, de Burlet, 1929, Wohlfahrt, 1932. Second, the 0° in-phase and 180° out-of-phase conditions in the previous study clearly differed from each other by the evoked motion pattern of this otolith with the rotational motion only identifiable under the 0° in-phase condition.…”
Section: Segmentation and Generating The 3d Surfacessupporting
confidence: 85%
“…In the case of the two-shaker setup, the distinct rotational motion of the glass catfish sagittae is suggestive of a quite effective separation of sound pressure and sound-induced particle motion in the tube at the tested frequencies (350 Hz,450 Hz). This rotational motion of the sagittae was expected based on our previous study in goldfish at the ESRF using a standing wave tube-like tank (Schulz-Mirbach et al, 2020) and according to former theoretical considerations (von Frisch, 1938, Freiin von Boutteville, 1935, de Burlet, 1929. In that study on goldfish, the 0° in-phase condition and thus the sound pressure maximum in the center of the tank induced the oscillation of the swim bladder walls which, in turn, resulted in the motion of the coupled Weberian ossicles and finally in a rotation of the saccular otoliths.…”
Section: Relationship Between Setup Conditions and Observed Motion Patternssupporting
confidence: 68%
See 3 more Smart Citations